Pengaruh Jarak Waktu Pemberian Pakan Konsentrat dan Hijauan Terhadap Produktivitas Kambing Peranakan Etawah Lepas Sapih - Iswoyo, Iswoyo; Widianingrum, Widianingrum (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The  objective  of  the study  was  to evaluate the  effect  of  concentrate  feeding  method  and  forage  on  PE  male  goat  productivity. Research  was  conducted  from October-December  2006 in  Satuan  Kerja Pembibitan  Ternak  Dinas  Sumber  Rejo, Kendal Regency.   Research  used 12 heads of post  weaning PE goat  with initial body  weight of 16.56  ±  2.64  kg.  Research  used  completely  randomized  design  (CRD) with  3  treatments  and  4  replications.  The  treatments  were (A) goat  given  concentrate together  with forage; (B) goat given concentrate and 2 hours afterward given forage; (C) goat given concentrate and 4 hours afterward given forage. Ratio consisting of  concentrate and field grass was given twice a day, in the morning and afternoon. Drinking water  was  given ad libitum.  Variable measured were dry matter (DM)  consumption,  average  daily  gain  (ADG) and feed  conversion. Result  of  the  research  showed  that DM  consumption,  ADG  and  feed  conversion in  every  treatment  shown  no  significance  (P  >0.05) statistically. However, treatment B tended to have higher ADG and lower feed conversion quantitatively. Treatments  A,  B  and  C  in  succession  showed  ration  consumption  of   698.01;  735.20  and  727.81 g/head/day; ADG of  44.08; 46.28 and 43.31 g/head/day, and feed convertiont  15.84; 15.89 and 16.81.